Thermodynamic and artificial intelligence-based performance analysis of parabolic vacuum tube solar collector assisted greenhouse drying system (vol 75, 107129, 2025) - Das, Mehmet; Pektezel, Oguzhan; Simsek, Mithat; Akpinar, Ebru (Elsevier, 2025)
[Abstract Not Available]